Reposisi Akal Sebagai Sumber Dalil Ekonomi Islam - Ubbadul Adzkiya'; Ahmad Lukman Nugraha; Mustofa Hasan (Jurnal Ilmiah Ekonomi Islam, 2022)
The author aims to define sense as a source of argument in Islamic law. The author tries to remap the position of sense as a source of argument for Islamic economic studies. The research method used in this study is a descriptive qualitative method using a literature study with a literature review approach. The finding of this paper is that sense has an urgent position as a corelation medium between positive economics and normative verses. sense is the power of gathering knowledge in developing science. In history, the Mu'tazilah places hujjah al-aql in the first position of the source of evidence as the process of istinbath al-ahkam. Qur'an and Hadith as normative explanations of ilm dharury determined by sense. The development of Islamic economics is dynamic in order to deal with issues and problems that occur in society. In addition to the Qur'an, Sunnah and Ijma', sense has an urgent position in the development of Islamic economics, so that it is able to detect solutions to modern economic problems through the Qur'an and Sunnah texts.